Strengthening High School Students' Character through a Hypercontent E-Module Based on the Core Values of Pangudi Luhur - Niken Widowati Setyaning Tyas; Agus Efendi; Moh. Muchtarom (Journal of Educational Sciences, 2026)
The increasing character problems in high school students, such as bullying, low empathy, and weakened social awareness, indicate that conventional character education strategies have not been able to internalize values meaningfully. This study aims to develop and test the effectiveness of a hypercontent e-module based on Pangudi Luhur's Core Values as a digital medium to strengthen students' character. The study used a Design-Based Research approach through the stages of needs analysis, design, expert validation, limited trials, field trials, and reflection, involving 30 grade XII students of Pangudi Luhur Santo Yosef Surakarta High School as subjects. Data were collected through questionnaires, observations, reflective journals, self-assessments, peer assessments, and character pretests and posttests. The results showed that the e-module was in the very valid category (91.67%), was considered very practical by students, and was effective in increasing understanding of values, reflective attitudes, social behavior, and character commitment, especially in internalizing the value of pro-poor. It is concluded that the hypercontent e-module designed with the Self-Regulated Learning approach and the ARCS motivation model is an interactive, contextual, and sustainable digital learning solution for strengthening the character of high school students.